Implementasi Smart City di Negara Berkembang: Suatu Tinjauan Literatur - Diva Dwi Ayuningtyas; Hatifa Roza; Mei Diva Safitri; Boni Saputra; M. Fachri Adnan (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2026)
Smart city implementation in developing countries has expanded rapidly over the last decade; however, its success remains constrained by challenges that differ significantly from those faced by developed countries. This article aims to analyze the patterns of smart city implementation, identify the determinants of success and failure, examine existing research gaps, and propose an integrative analytical framework for the context of developing countries. The study employs a literature review method with a narrative-thematic approach, drawing on twenty scientific articles published between 2020 and 2025. The findings indicate that smart city implementation in developing countries is still largely dominated by technology-driven and digital governance approaches, with research heavily concentrated in more developed urban areas while paying limited attention to archipelagic regions and vulnerable groups. The key determinants influencing implementation include digital infrastructure inequality, fragmented governance and regulatory frameworks, limited human resource capacity, and low levels of social inclusivity and public participation. The review also identifies six major research gaps: gender inclusivity, smart city development in archipelagic and disadvantaged regions, long-term impact assessment, perspectives of non-digital citizens, comparative studies across ASEAN countries, and integrated evaluation frameworks. Based on the synthesis of these findings, this study proposes the “Tri-Nexus Smart City” framework, consisting of the Infrastructure Nexus, Governance Nexus, and Social Inclusivity Nexus as simultaneous prerequisites for successful smart city implementation in developing countries. These findings provide both theoretical contributions and policy implications for the development of more adaptive, inclusive, and sustainable smart city initiatives.